PENGARUH MEDIA DALAM KONFLIK PARTISIPASI POLITIK PADA PEMILIHAN UMUM 2019 DI KOTA BANDA ACEH DAN MEULABOH - Reni Juliani; Nurkhalis Nurkhalis; Rena Juliana (SOURCE : Jurnal Ilmu Komunikasi, 2019)
The media has now been used by politicians as campaign media to convey persuasive messages to the public. This is because media literacy has become a part of people's lives, so people can easily access information through the media, including information about the potential leaders they will vote for in elections. This study aims to elucidate the influence of the media on opposing political participation in the 2019 parliamentary elections in the cities of Banda Aceh and Meulaboh by questioning informants, including politicians, academics, political observers and the public. From this study, it emerged that the media played a major role in shaping identity politics. The topic of religion and race became the main topic that the media spread in the 2019 parliamentary elections in the cities of Banda Aceh and Meulaboh and that influenced the decision of the people to vote for their top candidates. Keywords: Media, Conflict, Participation, Politics